1979
DOI: 10.1111/j.2042-7158.1979.tb13482.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of receptors on postganglionic cholinergic neurons in the guinea-pig isolated ileum

Abstract: Dopamine, apomorphine, noradrenaline and isoprenaline reduced the response of the isolated guinea-pig ileum to exogenous acetylcholine by a maximum of 40 %. Propranolol reversed this inhibition whilst phentolamine and pimozide were ineffective, suggesting that the drugs were acting on a post-synaptic 8-adrenoceptor. The same agonists were more effective as inhibitors of the response to transmural electrical stimulation of the ileum, lower doses producing almost complete inhibition. This inhibition was partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 16 publications
(4 reference statements)
1
9
0
Order By: Relevance
“…Dopamine inhibited the responses to exogenous acetylcholine and to electrical field stimulation (Ennis et al, 1979;Gorich et aI., 1982). Whether or not the effects of dopamine and apomorphine, which also inhibits the response to electrical field stimulation, represent an interaction with specific dopamine receptors is controversial, as is presented in Section 4 of this chapter.…”
Section: Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine inhibited the responses to exogenous acetylcholine and to electrical field stimulation (Ennis et al, 1979;Gorich et aI., 1982). Whether or not the effects of dopamine and apomorphine, which also inhibits the response to electrical field stimulation, represent an interaction with specific dopamine receptors is controversial, as is presented in Section 4 of this chapter.…”
Section: Motilitymentioning
confidence: 99%
“…Thus, it appears that in the guinea pig ileum the dopamine responses are mediated by adrenoceptors. This is controversial, as others have suggested that the guinea pig ileum contains two populations of prejunctional receptors on cholinergic neurons, one of which is an adrenoceptor and the other a dopamine receptor (Ennis et al, 1979). Evidence for adrenergically mediated dopamine responses is also available from isolated opossum duodenal longitudinal smooth muscle, where the responses were abolished by either phenoxybenzamine or phentolamine in each preparation tested (Anuras, 1981).…”
Section: Evidence Against Dopamine Receptors In the Gastrointestinal mentioning
confidence: 99%
“…It is conceivable that ascending release of ACh during the local distension may be modulated presynaptically through a-adrenergic re ceptors (8)(9)(10)(11). The investigation of this possibility, however, need further experi ments.…”
Section: Accepted May 25 1982mentioning
confidence: 99%
“…Dopaminergic receptor had recently been subclassified into DA-1 and DA-2 types (Hilditch & Drew 1985). In the guinea-pig ileum, inhibition of cholinergic twitch responses to field stimulation by dopamine was introduced as an action of DA receptors (Ennis et al 1979). Detailed pharmacological analysis of this effect led to the conclusion that it is mediated through a-adrenoceptors on cholinergic neurons (Gorich et al 1982;Zar et al 1982).…”
Section: Introductionmentioning
confidence: 99%